Aortic blood pressure and arterial stiffness in patients with controlled resistant and non‐resistant hypertension. Issue 2 (12th February 2020) - Cai, Anping; Siddiqui, Mohammed; Judd, Eric K.; Oparil, Suzanne; Calhoun, David A.
Abstract: The purpose of the current study was to determine whether aortic blood pressure (BP) and arterial stiffness are greater in patients with controlled resistant hypertension (RHTN) than controlled non‐resistant hypertension (non‐RHTN) despite similar clinic BP level. Participants were recruited from University of Alabama at Birmingham (UAB) Hypertension Clinic. Controlled hypertension was defined as automated office BP measurement with BP < 135/85 mm Hg. A total of 141 participants were evaluated by pulse wave analysis (PWA) and carotid‐femoral pulse wave velocity (cf‐PWV). Among them, 75 patients had controlled RHTN with use of 4 or more antihypertensive medications and 56 patients had controlled non‐RHTN with use of 3 or less antihypertensive medications. Compared to patients with controlled non‐RHTN, those with controlled RHTN were more likely to be African American and had a higher prevalence of diabetes mellitus and congestive heart failure. The mean number of antihypertensive medications was greater in patients with controlled RHTN (4.4 ± 0.8 vs 2.3 ± 0.7, P  < .001). Clinic brachial BP, aortic BP, augmentation pressure (AP), augmentation index normalized for heart rate of 75 beats per minute (AIx@75) and cf‐PWV were similar in both groups. In summary, there was no significant difference in central BP or arterial stiffness between patients with controlled RHTN and controlled non‐RHTN. These findings suggest that the higher residual cardiovascular risk observed in patients with RHTN after achieving BP control compared to patients with more easily controlled hypertension is not likely attributable to persistent differences in central BP and arterial stiffness.